Business Partners Associating Platform Based on Artificial Intelligence Tools - Bolek, Cezary; Grudzińska-Kuna, Joanna; Matusiak, Bożena Ewa; Papińska-Kacperek, Joanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
In the article, the conceptual model of artificial intelligence-based platform for business partners matching and associating is presented. Proposed solution is meant to be an alternative to traditional electronic trading B2B model offering automated heuristic approach to knowledge-based business partners selection problem. The key component of the model can be any artificial intelligence tool like genetics algorithm or neural network as it is presented in the paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 15-25